Reaction of arylboronic acids with 5-aryl-3-substituted-2-thioxoimidazolin-4-ones. Issue 49 (7th December 2016) - Dlin, Egor A.; Averochkin, Gleb M.; Finko, Alexander V.; Vorobyeva, Nataliya S.; Beloglazkina, Elena K.; Zyk, Nikolay V.; Ivanenkov, Yan A.; Skvortsov, Dmitry A.; Koteliansky, Victor E.; Majouga, Alexander G.
Graphical abstract: Highlights: Efficient route to novel S -aryl-3-substituted-2-thioxoimidazolin-4-ones via a copper catalyzed coupling reaction. Mild conditions with good to excellent yields in short reaction times. Potential applications in synthetic and medicinal chemistry as a novel class of p53/MDM2 inhibitors. Abstract: A convenient and efficient catalytic procedure for the selective S -arylation of 2-thioxoimidazolidin-4-ones to give novel S -aryl substituted 2-thiohydantoins under mild reaction conditions using arylboronic acids is described. The anticancer activity of the compounds were evaluated in vitro .